2011
DOI: 10.2139/ssrn.2379234
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Intra-Industry Trade and Adjustment Costs: The Australian Experience

Abstract: The objective of this research is to investigate labour market adjustment associated with changes in Australia's trade pattern over the period [1992][1993][1994][1995][1996][1997][1998][1999][2000] INTRODUCTIONTrade liberalisation and the resultant shifts in a country's trade patterns will be accompanied by significant resource reallocation effects. Transitional adjustment costs in factor markets will arise when markets fail to clear in response to changes in supply and demand conditions. More particularly, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 26 publications
1
17
0
2
Order By: Relevance
“…Focusing on Hungary, Ferto (2009) confirmed that industry-specific variables may have a significant effect on employment changes and the associated adjustment costs. Analysing Australian manufacturing industries, Thorpe and Lietao (2012) reported that the relationship between changes in employment and increased IIT indices supports the SAH proposition.…”
Section: Literature Reviewmentioning
confidence: 88%
See 2 more Smart Citations
“…Focusing on Hungary, Ferto (2009) confirmed that industry-specific variables may have a significant effect on employment changes and the associated adjustment costs. Analysing Australian manufacturing industries, Thorpe and Lietao (2012) reported that the relationship between changes in employment and increased IIT indices supports the SAH proposition.…”
Section: Literature Reviewmentioning
confidence: 88%
“…Over the years, empirical verification of the SAH to analyse the relationship between adjustments costs and different control variables emerged as a major area of research (Brulhart & Elliot, 1998; Brulhart & Thorpe, 2000; Ferto, 2009; Sarris et al, 1999; Tharakan & Calfat, 1999; Thorpe & Leitao, 2012). Several studies have used industry-level employment and industry’s total job turnover as a proxy for labour market adjustment process.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…puede ser un indicador de que una industria se encuentra en expansión y por lo tanto contratará a más individuos, lo que inducirá a mayores costos de ajuste porque entonces se desplazarán las personas hacia estas industrias desde otros sectores económicos. A pesar de que no se sabe con precisión cuál de los dos efectos es mayor, sí se puede deducir que mayores niveles de productividad ocasionan mayores variaciones del empleo intersectorial (Thorpe y Leitao, 2012). Thorpe y Leitao (2012) identificaron efectos marginales en la misma dirección para la economía australiana.…”
Section: Resultados Econométricosunclassified
“…De la ecuación [ ] 12 se puede observar que no importa si la variación es positiva o negativa para el empleo sectorial, dado que interesa que dicha variación sea menor cuando crece el comercio intra-industrial. Esta es la versión de costos de ajuste que se toma en este artículo para medir el impacto del comercio intra-industrial sobre las variaciones del empleo, lo que permite poner a prueba la HAS de forma correcta (Brülhart y Thorpe, 2000;Blanes, 2002;Erlat y Erlat, 2006;Thorpe y Leitao, 2012). Es importante mencionar que se debe tener sumo cuidado al momento de interpretar los efectos de otras variables independientes sobre las variaciones del empleo a la luz de la ecuación anterior, ya que efectos marginales positivos implican que el empleo sectorial varía (de forma positiva o negativa) mucho más que si el efecto marginal es negativo.…”
Section: Datos Y Variables Utilizadosunclassified